ANALYSIS OF MOTIVATION AND CAREER DEVELOPMENT ON THE PERFORMANCE OF EMPLOYEES OF THE MINISTRY OF MARITIME AFFAIRS AND FISHERIES JAKARTA - Peter Rajagukguk; Nurhadi; Dedi Supriadi; Seno Sudarmono Hadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the Influence of Career Development and Motivation on Employee Performance at the Ministry of Maritime Affairs and Fisheries at the Jakarta Apparatus and Organization Human Resources Bureau. This type of research uses quantitative descriptive research with a questionnaire method. The sampling technique uses saturated sampling where all members are used as a sample, namely 65 respondents. The results of the study showed that the regression equation Y = 20.532 + 0.338 X1 + 0.312 X2 partially had a positive and significant effect on employee performance. Simultaneously, career development and motivation had a positive and significant effect on employee performance with an R square value on the determination test of 0.494 so that career development and motivation affected employee performance at the Ministry of Maritime Affairs and Fisheries in the human resources bureau, apparatus and organization 49.4%, including the moderate category.